Grammatical Problems In Introduction Section Of Thesis Written By English Literature Students - Utami, Silvia (Lembaga Layanan Pendidikan Tinggi (LLDIKTI) Wilayah X, 2018)
Introduction section is the first section of the thesis that has an important role which summarizes background information about the topic. The ability to write a clear and concise introduction section of a thesis is indispensable skill to writers; thus it is essential for students to be aware of linguistic aspects of writing. Past literature in writing studies have shown that although many studies have been written about the grammatical errors and mistakes in writing, there is very little research done on grammatical problems in writing introduction section of thesis. This research was a descriptive qualitative research which aimed to analyze grammatical problems found in the introduction section of thesis written by English literature students at STIBA Persada Bunda Pekanbaru. The source of data in this research was documents taken from students’ thesis. The data were collected by using coding sheets. The findings of this research showed that the most common grammatical problems found in introduction section of thesis was incorrect verbs which dominated by tenses confusion and lack of subject and verb agreement. The possible solutions to overcome students’ grammatical problems were using indirect method in teaching grammar and prioritizing grammar structures to teach.